Clinical and diagnostic findings in patients with elevated cerebrospinal bilirubin. Issue 1082 (21st October 2015) - McCarron, Mark O; Lynch, Mark; McCarron, Peter; McCluskey, Gavin; McKee, Jacqueline; McVerry, Ferghal; O'Kane, Maurice J
ABSTRACT: Introduction: Cerebrospinal fluid (CSF) spectroscopy can identify subarachnoid haemorrhage (SAH) when CT is negative in patients presenting with acute severe headache. The primary objective of this study was to evaluate the clinical use and usefulness of CSF spectrophotometry. Secondary objectives were to identify other causes of elevated CSF bilirubin, to analyse headache descriptions and to compare clinical features in patients with an elevated CSF bilirubin among those with and without an intracranial vascular cause of SAH (avSAH). Methods: Consecutive patients admitted to two hospitals in Enniskillen and Londonderry between 1 January 2004 and 30 September 2014 with CSF spectroscopy bilirubin results were identified from a clinical chemistry laboratory dataset. Patients with elevated CSF bilirubin were studied. Clinical demographics, delays to investigation and final diagnoses were recorded. Patients with avSAH were compared with patients without avSAH. Results: Among 1813 patients with CSF spectrophotometry results, requests increased more than threefold during the study (p<0.001). Fifty-six patients had elevated CSF bilirubin. Ten (17.9%) had avSAH, of which 8 (14.3%) had aneurysmal SAH. Non-vascular causes of elevated CSF bilirubin included meningitis, spontaneous intracranial hypotension and carcinomatous meningitis. Headache descriptions varied. Time from headache onset to admission, CT scan and lumbar puncture did not differ significantly for patients with avSAH and non-avSAH. CSF red cell counts were higher among patients with avSAH than patients with non-avSAH (p=0.005). Conclusions: CSF bilirubin measurement has an important role in identifying avSAH in CT-negative patients presenting with a thunderclap headache. Better clinical selection of patients is required as CSF spectrophotometry, although sensitive, is not specific for SAH.